Analisis pengaruh pertumbuhan ekonomi dan pengangguran terbuka terhadap jumlah penduduk miskin di Kabupaten Tebo - Zurlinda Zurlinda; Purwaka Hari Prihanto; Jaya Kusuma Edy (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2020)
The purpose of this study was to determine and analyze: (1) the development of economic growth, open unemployment, and the number of poor people in Tebo Regency 2002-2015. (2) the development of poverty depth index and poverty severity index in Tebo Regency 2002-2015 period. (3) the effect of economic growth and open unemployment on the number of poor people in Tebo District 2002-2015. The method used in this research is the descriptive analysis method. The results of this study are economic growth and open unemployment in Tebo Regency for the period 2002-2015, which increased respectively by an average of 5.89% and 25.45% per year, then for the number of poor people in Tebo Regency in the 2002 period -2015 decreased by 1.36 percent. The results of this study also indicate a negative influence from the variables of economic growth and open unemployment on the number of poor people in Tebo Regency. Keywords : Economic growth, Open unemployment, The number of poor people